Design and Implementation of a Wireless Sensor Network for Smart Greenhouse Controller - Tung Le Van; Phuc Nguyen Thi; Phung Vo Minh; Le Do Thi; Huynh Le Cong; Tra Nguyen Thi Phuong (CommIT (Communication and Information Technology) Journal, 2022)
Sensors play an essential role in gathering environmental information for greenhouse farming. Wireless sensor network creates and manages links between sensor blocks in the system. As a result, not only various environmental parameters can be collected, but the sensor location can also be flexibly deployed. Sensor blocks require low energy consumption and inexpensive implementation costs with typical operating conditions. The research has built a wireless sensor network based on open Radio Frequency (RF) technology. Each sensor block has a low deployment cost and operates independently via a solar-powered unit. A novel communication protocol is designed for the proposed sensor network. In addition, a greenhouse controller exploiting designed wireless sensor networks is also constructed to evaluate the practicality of the system. Sensor networks developed are intended to be applied to the existing agricultural greenhouses in the surveyed area. The greenhouse is medium-sized, and the system implemented in practice is for vegetable farming. As a result, the controller can connect to the Internet to serve IoT links and applications. Experimental results prove the practicality of sensor blocks and the stability and efficiency of the wireless sensor network. It helps to reduce deployment costs and improve applicability. In addition, the sensor blocks are designed and built with low energy consumption, which can be operated with a small solar power source.